Familiarity and mating behavior in the subterranean rodent Ctenomys talarum (tuco-tuco) - Zenuto, Roxana Rita (2007)
Biological odors that convey cues regarding individual identity are known to alter mating behavior in some rodents. Deposition of chemical signals by males on the substrate could give females information about their neighbors’ identity and allow familiarization with their odors. This study tested whether familiarization of females with conspecific male odors affects mating behavior in Ctenomys talarum Thomas, 1898, facilitating mating as a consequence of a decrease in aggressive behavior and an increase in sexual behavior. Tuco-tucos are solitary subterranean rodents that occupy and defend adjacent burrows. Both sexes usually scent-mark burrow openings, providing odor signals to neighbors during their aboveground patrolling and foraging activities. Hence, familiarity by odor cues may represent an important mechanism that mediates neighbor recognition and probably mate selection. In this study, familiarity was established by housing females with male odors for 8 days. In C. talarum, individual recognition by olfactory cues may reduce mating costs when pairing with neighbors, since females showed low aggression towards familiar males and copulations were not repeated in consecutive days. Females that were not exposed to male odors were more aggressive, but surprisingly these pairs copulated repeatedly.